Karakterisasi Isolat JS-1, Bakteri Alkalofilik Penghasil Siklodekstrin Glikosiltransferase (CGTase) dari Sumedang, Jawa Barat - NUR MIFTAHURROHMAH; MOORDIANI MOORDIANI (Fakultas Farmasi Universitas Pancasila, 2014)
Cyclodextrin glycosyltransferase (CGTase) is an extracellular enzyme which is produced by some bacteria and archae that converts starch into cyclodextrin (CD). This enzyme has a high commercial value because of its product (CD) is widely used in several industries, such as pharmaceutical, chemistry, cosmetic, food, textile and also for environment protection. In Indonesia, there are still a few bacteria as CGTase producer were discovered and observed. The aim of this research was to find bacteria as CGTase producer from soil of corn farm land in Sumedang, West Java, and further characterized the isolate in produce CGTase. Horikoshi agar media was used as screening media. An alkalophylic bacteria as CGTase producer, JS-1 was successfully gained from this process. This isolate was characterized in the term of Gram staining, oxygen demand, motility and catalase test. The characterization results showed that JS-1 is a bacillus, Gram positive, facultative anaerob, motil and catalase positive. JS-1 isolate was also further characterized in order to determine optimum incubation period and temperature for CGTase production. The results were showed that JS-1 isolate was produced CGTase in maximum level if incubated for 48h at 37 °C.